Explanation of a Paradox in KrV B 137, AA 3, 111.25–28 - Caimi , Mario (Con-Textos Kantianos. International Journal of Philosophy, 2024)
The sentence of B 137 quoted in the title of this paper seems to pose a paradox incompatible with the theory of knowledge developed in the Critique of Pure Reason. In said sentence mention is made to “pure knowledge” independent of all sensibility, in spite of the fact that in the Critique it had been maintained that concepts without sensible content are empty, and that knowledge by mere concepts is impossible. Examination of how various interpreters attempt to remedy this paradox does not lead to a satisfactory result. Commentators have failed to take into account that the expression “knowledge”, which is part of the word “Verstandeserkenntnis”, stands in the neuter gender which is significant in this case, because it indicates that Kant did not want to refer to knowledge but to a decree (which is the meaning of “Erkenntnis” in the neuter gender, according to Grimm´s dictionary). Thus understood, the phrase ceases to be paradoxical and allows a more exact understanding of apperception.
Keywords: Transcendental Apperception; knowledge; cognition; concepts without content; I think; Kant